THE DISTRIBUTION AND THE RISK FACTORS OF ASYMPTOMATIC BACTERIURIA OF PREGNANCY IN THE OMSK REGION - Гордеева, Ирина Анатольевна; Кравченко, Елена Николаевна; Наумкина, Елена Витальевна (Mother and Baby in Kuzbass, 2018)
Purpose of the study – identification of the prevalence and risk factors of asymptomatic bacteriuria in pregnant women in the Omsk region. Materials and methods. The results of bacteriological examination of urine samples of 8000 pregnant women were analyzed, then the comparison groups were formed: the main group consisted of 100 patients with diagnosed low-grade asymptomatic bacteriuria who had not been treated; comparison group – 98 pregnant women with asymptomatic bacteriuria 105 CFU/ml; control group: 50 patients without asymptomatic bacteriuria. Statistical processing of the obtained results was carried out by the nonparametric statistics using Statistica 6.1. The reliability of the differences was determined by calculating the χ2 criterion at p < 0.05. Results. The most frequently detected clinically considered insignificant asymptomatic bacteriuria of 102-104 CFU/ml (12.3 %). Clinically significant bacteriuria with ≥ 105 CFU/ml was detected in 11.3 % of the examined. Moreover, in the first category of patients, especially in combination with risk factors, complications of gestation developed 5.4 times more often than in women with no bacterial growth in bacteriological urine, complications of childbirth and the postpartum period – 7.8 times, pathological changes in placental tissue and membranes – 2 times more often. Conclusion. Asymptomatic bacteriuria was registered in 23.6 % of the examined patients, and along with clinically significant bacteriuria, a low degree of the urinary tract contamination was also detected. In the presence of clinically insignificant asymptomatic bacteriuria (102-104 CFU/ml), especially in combination with other concomitant risk factors for the development of urinal tract infections (UTI), the complications of the course of pregnancy and childbirth are observed quite often, significantly exceeding the indices not only in the control group but also in the comparison group, that, probably, is connected with obligatoryness of antibacterial therapy at patients with a high degree of bacteriuria.